The Effect of Compensation and Work Culture on Employee Performance (Study at one of the conventional banks in West Java) - Hartati Maango; Zulkifli; Supriyanto (West Science Interdisciplinary Studies, 2023)
This research investigated the impact of nature exposure on mental health and well-being in West Bandung Regency, Indonesia, a region characterized by diverse natural landscapes. A mixed-method approach combining quantitative surveys and qualitative interviews was employed to gather data from residents of various communities in the area. The quantitative findings indicated that more frequent nature exposure was associated with lower levels of stress, anxiety, and depression. The qualitative insights revealed that nature exposure provided a sense of relaxation, tranquility, and rejuvenation, enhancing emotional well-being. The study underscores the restorative effects of nature and the importance of integrating green spaces into urban planning to promote mental health in rapidly developing regions like the West Bandung Regency.